Some Aspects of the Unification and Harmonization of the EU Private Law - E. A. Horrmann (Московский журнал международного права, 2012)
This article is dedicated to the theoretical and practical aspects of the unification and harmonization of the EU private law. The author gives the definitions of the key terms in this area as well as analyses and estimates the latest documents concerning unification and harmonization of the EU private law, such as Draft Common Frame of Reference of the Joint Network on European Private Law and Proposal for a Regulation Of The European Parliament And Of The Council on a Common European Sales Law.